A Socioeconomic and environmental description of the population of the Canto do Amaro oil field, in the state of Rio Grande do Norte, Brazil - Pinto Filho, Jorge Luís de Oliveira; Petta, Reinaldo Antônio; Souza, Raquel Franco de (Sustainability in Debate, 2016)
This article aims to describe the socioeconomic and environmental conditions of rural communities in the Canto do Amaro oilfield, in the state of Rio Grande do Norte, Brazil. The methodology included the application of a pre-test and a survey. Research results, that were statistically analyzed with SPSS software indicate that despite the economic importance of the region, the local population is subject to severe socio-economic constraints. A marked deficiency of environmental sanitation measures among the rural communities was also identified. Residents pointed out as main problems deficient water supply; the lack of garbage collection; the absence of sanitation; noise pollution; deforestation; waste of water; unemployment rates; violence; absence of street pavement; lack of schools; and precarious public lighting and electricity services. We conclude that it is necessary and essential to invest in sustainable and inclusive development strategies to avoid a future society marked by anomie and weak values.